Tanggung Jawab Perdata Korporasi Atas Kematian Gajah: Komparasi Hukum Indonesia dan Paradigma Ekosentrisme - Abdullah Azzam Alhudhaibi; Artaji Artaji (International Forum of Researchers and Lecturers, 2026)
The tragic death of a Sumatran elephant in a corporate concession area raises important questions about civil responsibility and environmental fairness. This article looks at the legal methods available in Indonesia to hold corporations accountable for the harm suffered by protected wildlife and compares this with the ecocentric perspective. Using a normative legal method with a comparative and conceptual approach, this study reviews how Indonesian law, which is grounded in human-centered views, treats elephants as state assets or legal objects. This setup requires the government or NGOs to sue for ecological or administrative losses. In contrast, the ecocentric model used in places like Ecuador and New Zealand recognizes nature as a legal entity with inherent rights to life and repair. The findings indicate that including ecocentric principles in Indonesia's civil law could change liability. This would allow guardians to sue specifically for restoring the elephant's habitat and addressing the inherent loss suffered by the species, rather than seeking only state financial compensation.